2021
DOI: 10.1002/iid3.422
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA Mirt2 upregulates miR‐1246 through methylation to suppress LPS‐induced lung cell apoptosis

Abstract: Introduction Long noncoding RNA Mirt2 has been proven to be a suppressor of lipopolysaccharide (LPS) (a key player in sepsis)‐induced inflammation responses. Therefore, Mirt2 may also participate in sepsis. This study was carried out to analyze the interactions between Mirt2 and microRNA‐1246 (miR‐1246) in sepsis, with a specific focus on sepsis‐induced acute lung injury (sepsis‐ALI). Methods Forty sepsis patients (sepsis group; 23 males and 17 females; 40–65 years, 48.6 ± 6.3 years), 40 sepsis patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The functions of these upregulated miRNAs are listed in Additional file 1: Table S1. Among these molecules, miR-1246, which showed the highest upregulation, has been proven to be involved in immune regulation [32], inhibition of angiogenesis [33], inhibition of cell apoptosis [34], promotion of cell migration [35], and promotion of M2 polarization of macrophages [36], and it is expressed at high levels during the chondrogenic differentiation of stem cells [37]; thus, miR-1246 potentially plays positive regulatory role in stem cell chondrogenic differentiation. Through GO enrichment analysis and KEGG enrichment analysis of the upregulated miRNAs, we found that these miRNAs are involved in various regulatory processes that are related to cartilage regeneration as well as the regulation of stem cell proliferation and chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of these upregulated miRNAs are listed in Additional file 1: Table S1. Among these molecules, miR-1246, which showed the highest upregulation, has been proven to be involved in immune regulation [32], inhibition of angiogenesis [33], inhibition of cell apoptosis [34], promotion of cell migration [35], and promotion of M2 polarization of macrophages [36], and it is expressed at high levels during the chondrogenic differentiation of stem cells [37]; thus, miR-1246 potentially plays positive regulatory role in stem cell chondrogenic differentiation. Through GO enrichment analysis and KEGG enrichment analysis of the upregulated miRNAs, we found that these miRNAs are involved in various regulatory processes that are related to cartilage regeneration as well as the regulation of stem cell proliferation and chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gao et al (8) showed that upregulated exosomal miR-1-3p can inhibit cell proliferation, promote apoptosis and cytoskeleton contraction, and increase the permeability of monolayer endothelial cells and membrane injury by targeting SERP1; consequently, the endothelial cells become dysfunctional, and the vascular barrier functions involved in the development of ALI may weaken. Moreover, a limited number of studies have investigated the modification of lncRNAs; for instance, Xu and colleagues (9) found that lncRNA Mirt2 suppresses LPS-induced lung cell apoptosis by upregulating miR-1246 through methylation. Zhou et al (10) used the serum of patients with sepsis (n = 85) and healthy controls (n = 76) to assess the diagnostic value of lncRNA H19 and established a sepsis-induced ALI rat model treated with lncRNA to determine the underlying molecular mechanisms.…”
Section: Roles Of Ncrnas In Cardiopulmonary Dysfunctionmentioning
confidence: 99%